2022
DOI: 10.4209/aaqr.220288
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Children's Exposure to PM2.5 and their Serum Inflammatory Responses in Taiwan

Abstract: PM2.5-induced inflammation have been demonstrated in the cellular and animal models, but few studies reported the associations of schoolchildren exposure to PM2.5 with their serum inflammatory biomarkers. Our goal was to examine whether serum inflammation was activated after children with long-term exposure to PM2.5 in an industrialized city of Taiwan. Schoolchildren (n = 183) between the ages of 6 and 12 years living in southern Taiwan were recruited to measure their serum inflammation including interferon-γ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Sigaud et al observed that neutrophils were released following exposure and inhalation of PM 2.5 in humans . The various inflammatory markers released include interferon-ϒ (IFN-ϒ), interleukin (IL)-4, IL-10, IL-12, and IL-13, along with the recruitment of eosinophils. , Disrupted calcium homeostasis is one of the significant mechanisms provoking disturbance due to PM 2.5 . As calcium is involved in the maintenance of normal cell physiology and functioning, increased levels can lead to stimulation of inflammation within the body and can cause damage to organs. , The toxic free radicals produced due to the inhalation of PM 2.5 lead to a subsequent increase in the levels of intracellular calcium (Ca 2+ ) ions, which can further aggravate the peroxidation process and ROS formation. , This could further lead to cell necrosis and delayed cellular apoptosis .…”
Section: Mechanisms Inducing Pm25-related Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sigaud et al observed that neutrophils were released following exposure and inhalation of PM 2.5 in humans . The various inflammatory markers released include interferon-ϒ (IFN-ϒ), interleukin (IL)-4, IL-10, IL-12, and IL-13, along with the recruitment of eosinophils. , Disrupted calcium homeostasis is one of the significant mechanisms provoking disturbance due to PM 2.5 . As calcium is involved in the maintenance of normal cell physiology and functioning, increased levels can lead to stimulation of inflammation within the body and can cause damage to organs. , The toxic free radicals produced due to the inhalation of PM 2.5 lead to a subsequent increase in the levels of intracellular calcium (Ca 2+ ) ions, which can further aggravate the peroxidation process and ROS formation. , This could further lead to cell necrosis and delayed cellular apoptosis .…”
Section: Mechanisms Inducing Pm25-related Complicationsmentioning
confidence: 99%
“… 31 The various inflammatory markers released include interferon-ϒ (IFN-ϒ), interleukin (IL)-4, IL-10, IL-12, and IL-13, along with the recruitment of eosinophils. 32 , 33 Disrupted calcium homeostasis is one of the significant mechanisms provoking disturbance due to PM 2.5 . As calcium is involved in the maintenance of normal cell physiology and functioning, increased levels can lead to stimulation of inflammation within the body and can cause damage to organs.…”
Section: Mechanisms Inducing Pm 25 -Related Compli...mentioning
confidence: 99%
“…Many reviews reported that the pollutants released from industrial activities are associated with many acute and chronic diseases (7,8). In particular, health effects of PM 10 and PM 2.5 exposure includes pulmonary disease, heart disease, chronic bronchitis, stroke, asthma, cancers and premature mortality (9,10). Similarly, numerous reviews reported that nitrogen dioxide (NO 2 ) exposure has also been linked to cellular inflammation, bronchial hyperresponsiveness, and an aggravated risk of infection predominantly in the respiratory and cardiovascular systems (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%